The mystery prizes - Pumpa, Helen; Liddell, Malcolm (Macmillan Education Australia South Yarra, 1998)
The Mystery Prizes by Helen Pumpa is an engaging children's book that follows a group of friends who stumble upon a series of mysterious clues leading to hidden prizes. As they embark on a thrilling treasure hunt, the young adventurers work together to solve puzzles and decipher riddles, fostering teamwork and problem-solving skills. Throughout their journey, they encounter unexpected challenges and learn valuable lessons about friendship, perseverance, and the excitement of discovery. With a blend of mystery and adventure, the story captivates young readers, encouraging them to think creatively and embrace the thrill of exploration.